The role of organisational climate in readiness for change to Lean Six Sigma. Issue 5 (9th October 2017) - Douglas, Jackie; Muturi, David; Douglas, Alexander; Ochieng, Jacqueline
Abstract : Purpose: The purpose of this paper is to examine the role of organisational climate in readiness for change (RFC) with particular focus on Lean Six Sigma (LSS) and to develop and operationalise an instrument to measure organisational climate to determine the organisational readiness of the Kenya Institute of Management (KIM) to progress to the next stage of the LSS implementation lifecycle. Design/methodology/approach: A case study outlining the KIM journey to LSS is described. A quantitative survey was developed based on the ten organisational climate dimensions discovered by Ekvall (1983) and redefined by Lauer (1994). This was then used to measure the climate of the case study organisation. Data were analysed to determine individual perceptions of the climate dimensions within KIM. The average score for each dimension was used to determine overall organisational performance and hence RFC. Findings: The generally positive scores across each dimension of the survey indicate that the KIM climate is ready for the next stage of its LSS implementation lifecycle although there may be some isolated pockets (individuals or groups) of resistance to change. However, the range of scores on each dimension indicates that there is disagreement within the survey group about the overall organisational climate. Research limitations/implications: The response rate to the climate survey questionnaire was only two-thirds of the total staff at KIM Headquarters and approximately one-fifth of all staff. The views of non-respondents are therefore not known and this may bias the results. Practical implications: Since climate influences RFC it is essential that an organisation can measure it to ensure its environment is conducive to the implementation of change generally and LSS particularly. The developed questionnaire is easy to use, easy to analyse and easy to interpret making it an ideal climate measurement instrument. Originality/value: Previous papers on LSS concentrate on organisational culture rather that climate as a success factor for LSS implementation. This paper addresses that omission.